Analysis of the Influence of Placement, Leadership, and Work Loyalty on Employee Performance at Bakesbangpol Aceh Tamiang - Sormin, Feddy Agustinus; Wahyudi, Hendy; Agusnarya, Luther; Adriyanto, Hasri; Fauzi, Ismart; Pane, Sri Gustina (Mahesa Research Center, 2025)
This study aims to analyze the influence of placement, leadership, and work loyalty on employee performance at the Aceh Tamiang National and Political Unity Agency (Bakesbangpol). The research method used is a quantitative approach with survey techniques. The data was collected through a questionnaire filled out by 61 employees, and analyzed using multiple linear regression. The results of the study show that partially, placement, leadership, and job loyalty have a significant effect on employee performance, with work loyalty having the greatest influence. The regression coefficients of each variable were 0.316 for placement, 0.398 for leadership, and 0.457 for work loyalty, all with a significance value of p 0.05. Simultaneously, these three variables also have a significant effect on employee performance, with an F-count value of 24.76 and an R² of 0.642, which means that 64.2% of the variation in employee performance can be explained by these three variables. This study concludes that proper placement, effective leadership, and high work loyalty together improve employee performance in Bakesbangpol Aceh Tamiang